Head Acceleration During A Simulated Match Load Of Tackles - Nichols, G.; Loh, N.; Lavender, Andrew; Rosalie, Simon; Davey, Paul; Netto, Kevin (2017)
This study aimed to determine the acceleration of the head relative to the thorax during rugby tackles and to examine the relationship between this acceleration and neck strength. Six state-level rugby players were randomly paired and engaged in 15 repeated front -on tackle s. High speed motion capture recorded head movement while neck strength was measured in an isokinetic dynamometer. Mean (SD) peak head acceleration for the ball carrier and tackler were 4.2g (±4.6) and 19.8g (±10.9) respectively. Correlation analyses showed the higher the flexion to extension neck strength ratio the lower the acceleration for the tackler only (r = 0.98). There is a much greater risk of being exposed to high accelerations of the head relative to the thorax for the tackler compared to the ball carrier. Further, minimising the strength difference between the neck flexors and extensors may have an effect of reducing head acceleration during a tackle